Identify the Use of Economics for Family Financial Management in Digital Days - Cicik Wijayanti, Tri; Naim, Sidrotun; Hendayani, Nenden; Alfiana, Alfiana; Hanum, Filia (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This paper examined the significance of economics in family financial management, specifically in the context of the digital era. The study employs a literature review approach to explore past research findings and insights related to the subject matter. The past tense is utilized to discuss previous studies and their implications. The literature review reveals that economics plays a crucial role in assisting families in navigating the complexities of financial management in the digital age. The widespread adoption of digital technology has revolutionized various aspects of personal finance, presenting challenges and opportunities for families. Past studies have highlighted the importance of economic concepts, such as budgeting, saving, investment, and consumer behavior, in achieving financial well-being. These concepts remain relevant today, but the digital landscape has influenced their application. Integrating digital tools and platforms has made financial transactions more accessible, streamlined, and convenient. However, it has also brought forth new risks, such as cybersecurity threats and the potential for impulsive spending. Furthermore, the literature emphasizes the need for families to develop digital financial literacy and skills. Understanding online banking, digital payment methods, and personal financial management apps is crucial for effective financial decision-making. Studies suggest that families that embrace digital tools for budgeting and expense tracking experience improved financial management outcomes.